Protecting Milk Supply During the COVID-19 Pandemic. Issue 5 (September 2020) - Spatz, Diane L.
Abstract : During the pandemic, supporting needs of childbearing families and the role of human milk as a lifesaving medical intervention should not be forgotten. International organizations such as the United Nations Children's Fund and the World Health Organization have recommended early, exclusive breastfeeding and skin-to-skin contact during COVID-19 including women who are positive for the virus. Our breastfeeding expert, Dr. Spatz, offers details of these recommendations.